2021
DOI: 10.3389/fcimb.2021.747135
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin 2 Is a Regulator During Macrophage Polarization Induced by Soluble Worm Antigens

Abstract: Caused by schistosomes, the human schistosomiasis is a tropical zoonotic parasitic disease. Pathologically, it occurs most often in the intestines and the liver, the sites of Schistosoma japonicum egg accumulation. The parasites’ produced eggs cause the main pathology in patients. Deposited parasite eggs in the liver induce the production of multiple cytokines that mediate the immune response, which in turn leads to granulomatous responses and liver fibrosis. These impact the hosts’ quality of life and health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Aiming to understand which mechanisms lead SWAP to induce polarization of the M1 profile, Shen et al . ( 2021 ) demonstrated that this antigen promoted the expression of a protein called lipocalin 2 (LCN2) and, consequently, induced the M1 profile of macrophages ( Table 2 ) through the upregulation of the NF- κ B signalling pathway. It has already been reported that this protein is increased in macrophages and can potentiate the M1 phenotype of microglia in the central nervous system (Jang et al ., 2013 ).…”
Section: Worm Antigens Can Induce An M1 or M2 Profilementioning
confidence: 99%
“…Aiming to understand which mechanisms lead SWAP to induce polarization of the M1 profile, Shen et al . ( 2021 ) demonstrated that this antigen promoted the expression of a protein called lipocalin 2 (LCN2) and, consequently, induced the M1 profile of macrophages ( Table 2 ) through the upregulation of the NF- κ B signalling pathway. It has already been reported that this protein is increased in macrophages and can potentiate the M1 phenotype of microglia in the central nervous system (Jang et al ., 2013 ).…”
Section: Worm Antigens Can Induce An M1 or M2 Profilementioning
confidence: 99%